ANALYSIS OF ROAD LIGHTING IMPACT ON ROAD USER SAFETY: CASE STUDY OF JALAN JATIBARANG-JATITUJUH - Bangkit Yanuar Yularso Candra; Amanatullah Savitri (Fakultas Teknik Sipil dan Perencanaan, 2024)
Despite the significant impact of street lighting on road user safety, there is a lack of monitoring for compliance with national standards (SNI) for many streetlights in West Java Provin The majority of accidents in the region result from factors such as overtaking, loss of vehicle control, tire blowouts, inadequate lighting, and unexplained incidents or brake failures. The Jatibarang-Jatitujuh Road is an example where lighting is neglected despite its susceptibility to high-speed traffic. The spacing between streetlights on this route, commonly used to connect Kabupaten and Kota Indramayu, is considerable, and tree branches obstruct some. Despite being a winding road prone to accidents, the Jatibarang-Jatitujuh Road remains busy with passing vehicles, especially at night. Poor street lighting contributes to the heightened risk for road users. Respondents express dissatisfaction with the illumination on the Jatibarang-Jatitujuh road, with an average satisfaction level of 6.73. Conversely, the importance level averages 9.1, indicating a high significance level and possibly exceeding respondents' expectations. The graphical analysis highlights vital indicators in each quadrant, with high-priority aspects including Road Lighting for safe driving, Road Lighting for road crossers, Road Lighting for road crowds, Road lighting for bridges, Road Lighting to mitigate the risk of road damage, Road Lighting for pedestrians, Road Lighting for uphill and downhill roads, and Road Lighting for driver's vision.